Impact of maturity stage and prolongation of post-harvest processing and mucilage fermentation time on mycotoxin levels in coffee - Osorio, Valentina; Montoya, Esther Cecilia; Rayo-Mendez, Lina María; Harris, Gabriel Keith (Frontiers in Plant Science, 2026)
Different wet processing conditions generate changes in the quality characteristics of the coffee beans. Currently, the primary sources of these changes are the exocarp and mesocarp, and processing times are increased before pulping and during the fermentation of mucilage for this purpose. This research evaluated the mycotoxin contents of fruit at three different stages of maturity (MS1, MS2, and MS3), subjected to times and two temperatures of 15 and 20°C, under fruit reserve and prolonged fermentation conditions. No significant differences were detected at the maturity stage, with ochratoxin values of 2.89, 2.98, and 3.03 μg/kg for MS1, MS2, and MS3, respectively, and the average aflatoxin concentrations were 0.13 μg/kg, 0.14 μg/kg and 0.15 μg/kg, respectively. For the fruit reserve treatments associated with stages MS1, MS2 and MS3, the ochratoxin contents were 3.05, 3.19 and 3.27 μg/kg, respectively. The maximum observed for the reserve treatments was 3.31 μg/kg in MS3, with a temperature of 20°C and a reserve time of 48 hours. The maximum average value observed for the treatments with prolonged fermentation was 3.51 μg/kg in MS2, with a temperature of 20°C and a prolonged fermentation time of 20 hours. These values indicate that regardless of processing delays, the initial quality of the fruit is critical to ensure the safety of the bean. The elimination of dry and defective fruit through different classifications followed by continuous drying prevents the development of the conditions necessary for the generation of mycotoxins.